Pengaruh Harga, Kualitas Produk Dan Promosi Terhadap Minat Pengguna E- Commerce Shopee Pada Mahasiswa Di Sekolah Tinggi Ilmu Ekonomi Bentara Persada - Sadewo , Yusup Yogi; Junianto , Pilifus; Atmojo , Agus Sekti Susila (Tractare: Jurnal Ekonomi-Manajemen, 2025)
ABSTRACT This study aims to determine the effect of price, product quality and promotion on buying interest in Shopee e-commerce users among students at Bentara Persada College of Economics both partially and simultaneously. This study uses quantitative research methods, whose data collection techniques use questionnaires. The sampling technique used in this study was a saturated sample distributed to 60 respondents who were Shopee e-commerce user students at Bentara Persada College of Economics Batam. Instrument Test in this study using Validity Test and Reliability Test and Classical Assumption Test in this study using Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test processed with SPSS version 26. The results of data processing on the price variable found that the tcount of -0.851 < t table of 2.00 with a significant level of 0.854 > 0.05, so the price has no positive and significant effect on purchase intention. The product quality variable produces a tcount value of 6.076 > t table of 2.00 with a significant level of 0.000 < 0.05, so product quality has a positive and significant effect on customer loyalty. The promotion variable produces a tcount value of 2.891 > t table 2.00 with a significant level of 0.005 < 0.05, so promotion has a positive and significant effect on customer loyalty. From the F test it is known that the Fcount value of price, product quality and promotion is 91.508 > Ftable 2.77 with a significant value of 0.000 <0.05. From the R2 test it is found that price, product quality and promotion contribute 83.1% to buying interest, while the remaining 16.9% of buying interest is influenced by other independent variables not explained in this study. Year 2025